2013
DOI: 10.7324/japs.2013.3809
|View full text |Cite
|
Sign up to set email alerts
|

Influence of adipose tissue derived mesenchymal stem cells in combination with injectable bone substitute on osteoclastogenesis in osteoporotic rats

Abstract: The present study was designed to evaluate the influence of adipose tissue derived mesenchymal stem cell (ASCs) with or without calcium phosphate composite on osteoclastogenesis in osteoporotic rats. Mesenchymal stem cells (MSCs) were harvested from adipose tissue of both the omentum and the inguinal fat pad of male rats, as the sex mismatch, to track the MSCs fate and to ensure their homing to the injured females' femurs. The isolated ASCs were characterized via the morphological appearance, multilineage pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…(A–C) Showing BM‐MSCs differentiated into osteocytes, adipocytes and chondrocytes. (D–F) Showing adipose derived MSCs differentiation into osteocytes, adipocytes and chondrocyte.…”
Section: Resultsmentioning
confidence: 99%
“…(A–C) Showing BM‐MSCs differentiated into osteocytes, adipocytes and chondrocytes. (D–F) Showing adipose derived MSCs differentiation into osteocytes, adipocytes and chondrocyte.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, differentiation of BM-MSCs and AD-MSCs through adipogenesis chondrogenesis and osteogenesis was confirmed by using Alizarin Red S stain, Oil Red O stain and Alcian Blue stain, respectively. (23,24) Flow cytometry findings showed that BM-MSCs were positive for CD44 (77.1±18.1) and CD105 (78.7±16.3) and negative for CD34 (1.62±0.43). Also, AD-MSCs characterization using flow cytometry showed CD44 positive (81.2±19.6) and CD105 positive (74.3±16.9), but CD34 negative (3.05±0.71).…”
Section: Discussionmentioning
confidence: 99%